IOT integrated smart grid management system for effective energy management. (December 2022) - Madhuri, N.S.; Shailaja, K.; Saha, Debasmita; P, Revathy; Glory, K.B.; Sumithra, M.
Abstract: Customers' steadily increasing usage of power equipment causes a mismatch among requirements and supply, which presents a growing issue for power generation. Energy management is an essential tool in minimizing large supply-side shortages and boosting power effectiveness. The present practice in energy systems emphasizes lowering the total price of electricity without restricting use by deciding to decrease electricity usage duringpeaktimings. The aforementioned problem calls for the creation and advancement of an adaptable & moveable technology that serves a broad range of clients and maintains the overall energy balance. The goal of the Intelligent Electricity Management Solution seems to be to compensate for an energy loss of electricity in a territory with managed part-load reduction that caters to consumption habits. The execution of experiments conducted is demonstrated under the assumptions of a power storage occurrence, the maximum demand restriction using various scenarios, and adjusting the preference allocated to each equipment. In Intelligent Power Management System (IPMS), there are price-optimization techniques depending on the duration of use and flexibility using detector information elements. A home location network with efficient ZigBee connectivity has been constructed, and an IoT framework has been created for predictive analytics and archiving.